Pak-Stanley labeling of the m-Catalan hyperplane arrangement - Duarte, Rui (2021)
We characterize in simple terms the Pak-Stanley labels λ(R) of the regions R of the m-Catalan arrangement. We also propose a simple algorithm that returns R from λ(R). Finally, we characterize in close terms the labels of the relatively bounded regions.